2011
DOI: 10.1128/mcb.00801-10
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Factor Cwc22 Is Required for the Function of Prp2 and for the Spliceosome To Escape from a Futile Pathway

Abstract: Cwc22 was previously identified to associate with the pre-mRNA splicing factor Cef1/Ntc85, a component of the Prp19-associated complex (nineteen complex [NTC]) involved in spliceosome activation. We show here that Cwc22 is required for pre-mRNA splicing both in vivo and in vitro but is neither tightly associated with the NTC nor required for spliceosome activation. Cwc22 is associated with the spliceosome prior to catalytic steps and remains associated throughout the reaction. The stable association of Cwc22 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 48 publications
5
37
0
Order By: Relevance
“…S7). Cwc22 is an integral protein of the B act complex and is required for the catalytic activation of the spliceosome Yeh et al 2011). As Cwc22 remains stably associated with the spliceosome during its catalytic phases and only leaves upon displacement of the mRNA, it could conceivably play a part in stabilizing the binding of the mRNA to the spliceosome.…”
Section: Discussionmentioning
confidence: 99%
“…S7). Cwc22 is an integral protein of the B act complex and is required for the catalytic activation of the spliceosome Yeh et al 2011). As Cwc22 remains stably associated with the spliceosome during its catalytic phases and only leaves upon displacement of the mRNA, it could conceivably play a part in stabilizing the binding of the mRNA to the spliceosome.…”
Section: Discussionmentioning
confidence: 99%
“…33 Our screen revealed that siRNAs against several spliceosome components resulted in increased cell survival in the presence of taxol. 10 The spliceosome components uncovered in our screen included: SNRPB (SmB/B'), one of 7 core structural spliceosome proteins that directly assemble on the U-rich snRNAs; 34 P14 (SF3B14), a protein that directly contacts the adenosine at the branch point and carries out the first transesterification reaction during splicing; 35 as well as the spliceosome associated components CWC22 36 and CRNKL1. 37 To understand how depletion of these spliceosome components increased cell survival in taxol, we transfected HeLa cells with a pool of 4 siRNAs designed against each of the indicated spliceosome components.…”
Section: Depletion Of Spliceosome Components Induces Cell Cycle Delaysmentioning
confidence: 99%
“…Prp2 is at the center of a network of interactions, directly contacting the Sf3 protein Ysf3 (39) as well as Cwc22 and Spp2. Cwc22 is essential for Prp2 function: In its absence, hydrolysis of ATP by Prp2 simply results in the release of Prp2 without promoting the first chemical step (40). Spp2 interacts directly with Prp2 and is released upon ATP hydrolysis (41).…”
Section: Dead Box Proteinsmentioning
confidence: 99%